Mitotic block and epigenetic repression underlie neurodevelopmental defects and neurobehavioral deficits in congenital heart disease - George C. Gabriel; Hisato Yagi; Tuantuan Tan; Abha Bais; Benjamin J. Glennon; Margaret C. Stapleton; Lihua Huang; William T. Reynolds; Marla G. Shaffer; Madhavi Ganapathiraju; Dennis Simon; Ashok Panigrahy; et al. (Nature Communications)
Abstract Hypoplastic left heart syndrome (HLHS) is a severe congenital heart disease associated with microcephaly and poor neurodevelopmental outcomes. Here we show that the Ohia HLHS mouse model, with mutations in Sap130, a chromatin modifier, and Pcdha9, a cell adhesion protein, also exhibits microcephaly associated with mitotic block and increased apoptosis leading to impaired cortical neurogenesis. Transcriptome profiling, DNA methylation, and Sap130 ChIPseq analyses all demonstrate dysregulation of genes associated with autism and cognitive impairment. This includes perturbation of REST transcriptional regulation of neurogenesis, disruption of CREB signaling regulating synaptic plasticity, and defects in neurovascular coupling mediating cerebral blood flow. Adult mice harboring either the Pcdha9 mutation, which show normal brain anatomy, or forebrain-specific Sap130 deletion via Emx1-Cre, which show microcephaly, both demonstrate learning and memory deficits and autism-like behavior. These findings provide mechanistic insights indicating the adverse neurodevelopment in HLHS may involve cell autonomous/nonautonomous defects and epigenetic dysregulation.